Studies on the spin-state equilibria of cobalt ions in the system La1-x Na x Co1-x Nb x O3 (x≤0·40) - Parkash O.; Chaturvedi N.; Tiwari M.; Kumar D. (My University, 2025)
The spin-state equilibria of cobalt ions in the system La1-x Na x Co1-x Nb x O3 (x≤0·40) has been studied by measuring its magnetic susceptibility as a function of temperature in the range 300-600 K. It is found that the behaviour of the samples with x≤0·10 is similar to that of LaCoO3, while compositions with x≥0·20 behave quite differently, exhibiting simple paramagnetic behaviour. © 1989 Indian Academy of Sciences.